The indiscrete image : infinitude & creation of the human - Carlson, Thomas A. (Religion and postmodernism., 2008)
Humanity's creative capacity has never been more unsettling than it is at our current moment, when it has ushered us into new technological worlds that challenge the very definition of "the human." Those anxious to safeguard the human against techno-scientific threats often appeal to religious traditions to protect the place and dignity of the human. But how well do we understand both theological tradition and today's technological culture? In The Indiscrete Image, Thomas A. Carlson challenges our common ideas about both, arguing instead that it may be humanity's final lack of definition that